Influence of Disulfide Bridge on the Structural Stability of Human Neuroglobin: A Molecular Dynamics Simulation Using Latest Data Entry - Quyen, Bui Thi Le; Hoai, Nguyen Thi Lam; Thanh, Ngo Van (Communications in Physics, 2016)
In this paper, we investigated the role of the disulfide bridge in the structural stability of wild-type human neuroglobin. The classical simulation of the neuroglobin without the disulfide bridge was performed for a long simulation run of 240~ns   using a new parameter set of Gromos96 force field and the latest data entry as the initial topologies. We used the analyzed data of original neuroglobin with the remained disulfide bridge to compare to the ones from this simulation. Our results showed that, the structure of neuroglobin was still very stable although the disulfide bridge was absent. There was only a few residues in B and C helices having a higher mobility. The most interesting result we obtained was that the increasing distance between the distal histidine and heme group could allow oxygen to bind more easily